MAN FROM ATLANTIS. (From Abba to Zoom: A Pop Culture Encyclopedia of the Late 20th Century, 2005)
Information is presented on the science fiction television series "Man From Atlantis," telecasted from 1977-1978. The series starred Patrick Duffy as amphibious humanoid Mark Harris, the only surviving inhabitant of the fabled lost continent. Harris was equipped with superhuman powers. He had the capacity to breathe underwater, and swim like a fish.